Prognostic variables associated with biochemical recurrence following radical prostatectomy for pT3b prostate cancer: a research study - Ulanbek Zhanbyrbekuly; Jung Kwon Kim; Minyong Kang; Bumsik Tae; Ja Hyun Ku; Hyeon Hoe Kim; Chang Wook Jeong (National Scientific Medical Center, 2018)
Objectives: The objectives of the current study were to determine long-term biochemical recurrence rates stratified by adverse pathologic features and to identify predictive factors of biochemical recurrence rates following radical prostatectomy performed by either retropubic prostatectomy or robot-assisted laparoscopic prostatectomy from single tertiary center prostate cancer database. Material and Methods: The Seoul National University Hospital prostate cancer database was queried for all patients treated with radical prostatectomy from 1999 to 2015. Among the 2680 patients who underwent radical prostatectomy, 331 patients with seminal vesicle invasion (pathologic T3bN0-1M0 stage) were identified. The primary endpoint was biochemical recurrence, defined as two consecutive postoperative prostate specific antigen values ≥0.2 ng/ml. Comparative analysis based on adverse pathologic characteristics and operation type was performed. Results: Five and 10-year biochemical recurrence-free survival in the entire cohort was 59.0% and 42.9%. The Kaplan-Meier survival analysis demonstrated 5-year biochemical recurrence free survival rates differences in patients with different lymph node involvement (70.6% vs. 52.4%, log-rank, p=0.01). Variables including age, extracapsular extension, lymph node invasion, surgical margin, perineural invasion, multicentricity and Capra-S score were similar between the groups of patients who underwent either retropubic or robot-assisted laparoscopic radical prostatectomy. The mean prostate specific antigen level, seminal vesicle invasion laterality, tumor volume, and pathologic Gleason score were lower in the cohort of patients who underwent robot-assisted laparoscopic prostatectomy. No statistically significant differences were found in 5-year biochemical recurrence-free survival rates stratified by operation type (58.1% vs. 65%, log-rank, p=0.8), by Capra-S score (72.5% vs. 56.8%, log rank, p=0.1), or by surgical margin status (69.4% vs. 59.3%, log-rank, p=0.8). In univariate and multivariate Cox proportional regression analysis lymph node involvement (p=0.01) was found to be a statistically significant predictor of biochemical recurrence. Conclusion: Patients with positive lymph node involvement have a poor prognosis. Capra-S score was unable to predict biochemical recurrence in patients with pathologic T3b stage prostate cancer. Robot-assisted laparoscopic prostatectomy is comparable to retropubic radical prostatectomy in terms of the biochemical progression of prostate cancer with seminal vesicle invasion.